The development and modelling of high intensity impinging stream jet reactors for enhanced mass transfer in gas-liquid systems - Kleingeld, Anton W. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1999.